Evaluation of water footprint of selected crop consumption in Tehran province - Rezaei Kalvani, S.; SHARAAI, A.; MANAF, L.; HAMIDIAN, A. (ALÖKI Applied Ecological Research and Forensic Institute, 2019)
The sharp increase in water consumption poses a risk of increasing water scarcity in developing countries. The aim of this study is to the quantify variability of per capita Water Footprint (WF) of consumption of selected crops in Tehran province from 2008–2014. Blue and green WF were computed using WF approach. Besides, per capita WF of crop consumption was evaluated using bottomup approach. The result illustrated the external water footprint had the largest contribution in total WF of crops consumption in the Tehran province (2008-2014). The total water footprint of crop consumption decreased because the population and per capita WF also decreased. Besides, wheat and rice had the largest per capita WF. This study discloses that it is essential to have appropriate water management to reduce water stress originating from agricultural sector in future. The consumption of wheat in Iran is high, more precisely 2 times larger than global average. It is recommended to reduce the consumption of wheat in Tehran or replace it with other crops. Besides that, decision makers in agricultural sector should reduce water lost, with declining production of cherry, pear, and peach. Furthermore, reducing water footprint of crops and efficient agricultural water management are recommended